Immunogenicity of Vibrio vulnificus capsular polysaccharides and polysaccharide-protein conjugates. - Simonson, J G (1993)
Opaque colony morphology has been correlated to Vibrio vulnificus virulence. However, the number of capsular serotypes expressed by virulent isolates is unknown. In an effort to produce anticapsule sera, capsular polysaccharide (CPS) from three opaque V. vulnificus strains was purified and characterized. Purified CPSs were acidic and contained considerable amounts of hexosamine and trace quantities of protein and nucleic acid. CPS purified from strain C7184 was poorly immunogenic for rabbits and mice, since repeated injection produced little detectable anticapsular antibody. To improve immunogenicity, CPS-protein conjugates were prepared from adipic acid hydrazide derivatives of CPS purified from each strain and carbodiimide as a coupling reagent. The immunogenicity of C7184 CPS was enhanced by conjugation to keyhole limpet hemocyanin, since injection into mice elicited production of anticapsular antibodies, the level of which was dependent on the dose and time since initial immunization. Injection of rabbits with CPS-protein conjugates also produced anticapsular antibodies. Staphylococcus aureus cells armed with each of the three anticapsular antibodies coagglutinated only the homologous opaque strain, indicating the existence of at least three capsular types. Further screening of 32 opaque and translucent V. vulnificus isolates revealed only three cross-reacting strains. These results suggest the presence of numerous V. vulnificus capsular types.